Gamifikasi Pembelajaran Menulis Teks Eksplanasi untuk Siswa Kelas XI SMA - Caesar Adlu Hakim; -, Didin Widyartono (UNIB Press, 2024)
This study aims to develop classcraft-based gamification learning in learning to write explanatory texts for grade XI SMA. This research uses the ADDIE model which consists of 5 stages, namely (1) analyze with the stage of analyzing field needs (2) design with the stage of designing products by compiling an outline of media development and lesson plans, (3) development with the stage of developing classcraft products which are then validated by Indonesian language learning material and media experts, (4) implementation with the stage of practitioner testing by two Indonesian language teachers and trials with two stages, namely small group tests and large group tests, and (5) evaluation with the stage of revising the product according to expert and practitioner validation input. The subjects of this research were the XI grade students of SMA Negeri 2 Ponorogo. The results of this study produced a classcraft-based gamification product for learning to write explanatory texts containing material for writing explanatory texts including explanatory text development patterns and how to write explanatory texts. The product developed was validated by material and media experts with an average score of 87.6% which was classified as very feasible. In addition, a practitioner test was conducted by two teachers which resulted in an average score of 91%. Then, a field trial was carried out with two stages, namely a small group test which obtained a result of 89.5% and a large group test which obtained a result of 90.6%. This research shows that classcraft-based gamification is very feasible and can be implemented in classroom learning.